STRATEGI PEMASARAN PRODUSEN LURIK PRASOJO - Fadhly Ahmadian Fadhly; Eni Setyowati (Universitas Muhammadiyah Surakarta, 2024)
Indonesia has many traditional cultural practices, including traditional lurik cloth, which originates from the Klaten region. This cloth is considered part of the culture of the Klaten people, and its use is still valid today. The development of the textile industry also influenced the use of lurik. Prasojo, the main producer of lurik, is a key player in the industry. The company has used lurik as a raw material since the 1950s. Marketing strategy includes positioning, product development, marketing budget, and promotion. Segmentation, targeting, and positioning are three key strategies that contribute to a company's success in marketing. Segmentation helps identify target audiences and create more focused and effective marketing strategies. In conclusion, Indonesia's cultural heritage is rich and diverse, with a variety of traditions and practices that contribute to a unique culture and identity.